Digital Tourism as a Digital Marketing Strategy for Blockbuster Museum Surabaya Tourism Destinations - Yudiana Indriastuti; Diana Amalian; Siska Armawati Sufa (Future Science, 2022)
The Covid-19 pandemic has had a huge impact on the tourism world. Tourism Industry Managers and Management are starting to shift marketing from offline to digital. One of them is the Surabaya Blockbuster Museum. The Blockbuster Museum is a tourist museum with the theme of toy collections of blockbuster movie characters, such as Captain America, Iron Man, Game of Thrones, Superman, Marvel, Star Wars, Disney, Harry Potter, several horror movie characters, Titanic, and many more. This study wants to find out more about the strategies implemented by the Blockbuster Museum in attracting tourist visits through digital marketing. This study uses a qualitative-descriptive type of research. The technique used in this research is In-depth Interview, Literature Study, Documentation, and Observation. Based on the results of the discussion, it can be concluded that the Surabaya Blockbuster Museum Manager utilizes marketing through digital media because it is considered efficient in reducing the promotional budget. MBS uses social media, Online Travel Agents (OTA), Influencers, Communities, and Local Toy Manufacturers. The social media used are Instagram, Facebook and Youtube, but the manager optimizes the use of Instagram more than other social media, one of the strategies carried out is by utilizing IG Ads to capture a wider target market. In addition, MBS also the manager also uses influencer services to attract the number of visitors from influencer followers, namely Merlianny Effendi (merli_sansan account), Asli Arek Suroboyo (originalareksuroboyo account) and Kuliner Nglencer (culinary_nglencer account). The management also conducts marketing through events by cooperating with the Infis Community (Independet Film Surabaya) and the Charity Superhero Community. Local toy manufacturers are also partners who are partnered by MBS management to hold joint exhibitions, the museum provides an exhibition space, while partners market local toy products at MBS, such as GGNW Toys and Dolanan Keren. The managing party utilizes various types of digital marketing and makes interesting event activities to be able to attract more tourist visits to the museum.